2016
DOI: 10.1007/s12035-016-0301-9
|View full text |Cite
|
Sign up to set email alerts
|

TAT-PEP Enhanced Neurobehavioral Functional Recovery by Facilitating Axonal Regeneration and Corticospinal Tract Projection After Stroke

Abstract: Paired immunoglobulin-like receptor B (PirB) has been identified as a new receptor for myelin-associated inhibitory (MAI) proteins, which may play important role in axonal regeneration and corticospinal tract (CST) projection associated with neurobehavioral function recovery after stroke. Here, we found that the expression of PirB was increased in the cortical penumbra from 1 to 28 days after transient focal cerebral ischemic reperfusion of rats. Then, transactivator of transcription-PirB extracellular peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…TAT-PEP, a recombinant protein consisting of PirB extracellular motif fused with TAT, which demonstrated the ability to rescue neurite outgrowth inhibition induced by Nogo, MAG and OMgp in stroke (Deng et al, 2016), was used to treat PC12 PirB . Results in Figure 2C showed that treatment with TAT-PEP effectively prolonged the growth of axon.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TAT-PEP, a recombinant protein consisting of PirB extracellular motif fused with TAT, which demonstrated the ability to rescue neurite outgrowth inhibition induced by Nogo, MAG and OMgp in stroke (Deng et al, 2016), was used to treat PC12 PirB . Results in Figure 2C showed that treatment with TAT-PEP effectively prolonged the growth of axon.…”
Section: Resultsmentioning
confidence: 99%
“…TAT-PEP (PirB extracellular peptide) construction, expression and purification were carried out as previously reported (Deng et al, 2016). Briefly, cDNA of extracellular domain of PirB was synthesized and cloned into expression vector pTAT-HA-6xHis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paired immunoglobulin‐like receptor (PIR)‐B, which is a well‐known receptor for major histocompatibility complex class I (MHCI) (Nakamura, Kobayashi, & Takai, 2004), has been identified as a novel receptor for these three MAIs and mediates induction of axonal growth inhibition by the MAIs (Atwal et al, 2008). PIR‐B is expressed in CNS neurons (Deng et al, 2018; Syken, Grandpre, Kanold, & Shatz, 2006). The expression of PIR‐B is drastically increased in injured CNS tissues (Adelson et al, 2012; Deng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%